On solvability of nonlocal boundary value problems for certain sets of evolutionary differential equations - Malovichko , V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
We establish strong solvability of nonlocal boundary value problems for two systems of evolution differential equations of third and fourth order.